2014
DOI: 10.1080/09540121.2014.894610
|View full text |Cite
|
Sign up to set email alerts
|

Improving cervical cancer screening rates in an urban HIV clinic

Abstract: HIV-infected women are at increased risk of invasive cervical cancer, however screening rates remain low. The objectives of this study were to analyze a quality improvement intervention to increase cervical cancer screening rates in an urban academic HIV clinic and to identify factors associated with inadequate screening. Barriers to screening were identified by a multi-disciplinary quality improvement committee at the Washington University Infectious Diseases clinic. Several strategies were developed to addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…25 This study's estimate is lower than that of those from high-income countries. [37][38][39] This difference can be due to delayed integration of cervical cancer screening programs with CTC services in Tanzania compared to high resourced countries. 31 Advice from health care providers was the main reason for cervical cancer screening among women in this study, as reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 This study's estimate is lower than that of those from high-income countries. [37][38][39] This difference can be due to delayed integration of cervical cancer screening programs with CTC services in Tanzania compared to high resourced countries. 31 Advice from health care providers was the main reason for cervical cancer screening among women in this study, as reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…25 This study's estimate is lower than that of those from high‐income countries. 37 , 38 , 39 This difference can be due to delayed integration of cervical cancer screening programs with CTC services in Tanzania compared to high resourced countries. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal HIV care may improves access to cancer care, however, Pap test is still underutilized among HIV-positive women [20] , [21] , [22] , [23] . Thus, efforts should continue to increase Pap test screening in this population, as well as the compliance with recent screening guidelines for female PLWHA from the American College of Obstetricians and Gynecologists [24] , which include HPV testing.…”
Section: Discussionmentioning
confidence: 99%
“…OPEN Research intervals to every 3 years following 3 consecutive Pap smears with normal results, and they included consideration of HPV cotesting, where available, for women with HIV who are older than 30 years. 21 Previous studies in high-income countries reported that only 29%-58% of women with HIV had been screened for cervical cancer in the previous 1-3 years, [22][23][24][25] with higher HIV viral loads and lower CD4 counts associated with longer delays. 24 Our primary objectives were to measure the prevalence of self-reported adherence to cervical cancer screening among women with HIV in Canada and to identify factors associated with delays in cervical cancer screening.…”
mentioning
confidence: 99%